Embeddedness as a Process - Chajewski, Leszek (Conference Papers -- American Sociological Association, 2005)
This article describes a strategy of modeling embeddedness of economic behavior as a process, as opposed to viewing it as a time-independent relationship between behavior and a social factor in which it is subsumed. I first reconstruct Polanyi's classic processual model of embeddedness and derive from it a set of intuitive tests, which are then applied to key modern approaches in economic sociology: structural, neo-institutional, neo-weberian and Fligstein's embeddedness-as-identity-formation approach. Finally, I describe main analytic and empirical consequences of the processual approach to embeddedness. Key among these consequences is that not all forms of embeddedness are of equal significance, therefore, economic sociology's empirical focus should shift from demonstrating that behavior is more likely to be embedded than not, to the forms of economic behavior that are likely to dominate alternative types of behavior.
Keywords: cultural and neo-weberian perspectives in economic sociology; economic sectors; economic systems; embeddedness; embeddedness and identity formation; embeddedness process; empirical research; forms of economic integration; market transitions; neo-institutionalism; new economic sociology; social factors; social status; socioeconomics

"Economic Life, Institutions, and Social Action: Reflections on Polanyi's Approach to Studying Economic Life" - Gemici, Kurtulus (Conference Papers -- American Sociological Association, 2005)
The article focuses on the relevance of economist Karl Polyani's economic theories and tries to analyze if his book titled "The Great Transformation," could be considered as the foundation of current economic sociology and international political economy. The author of the article says that Polayni's theories focuses on contemporary economic sociology, market economy's self-destructive approach and consideration of the market economy as integral part of the society. His work on institutedness and economy's embedness in society are working as base for most of the challenging theories in economic sociology.
Keywords: Great Transformation, The (Book); capitalism; economic behavior; economics; embeddedness; institutions; methodology; socioeconomics

Globalization - McMichael, Phillip (The Handbook of Political Sociology states, civil societies, and globalization, 2005)
Philip McMichael casts a critical eye on the process of globalization suggesting that it takes different forms across time and space. He specifies contemporary globalization as a discursive project, geared to institutionalizing corporate markets through multilateral and regional economic agreements driven by powerful states. From this perspective of depicting globalization as an exercise in power, he examines political countermovements to globalization. Global justice movements, he argues, are globalization’s “historical and relational barometer,” and they operate at various, but often interrelated, scales. Work- ing from Karl Polanyi’s “double movement” of implementation of and resistance to economic liberalism, McMichael questions the adequacy of Polanyi’s formulation for the elaboration of market rule in the twenty-first century. This question concerns the conventional interpretation of “sovereignty” as the centerpiece of nation-state formation, including the development of citizenship. Here, globalization is viewed through the lens of a sovereignty crisis, where corporate market rule compromises the social contract upon which the state/citizen relation is founded. The crisis is expressed differently across the world, as the impact of market rule generates alternative social movement conceptions of sovereignty, especially in the global south where corporate globalization is realized through a drastic intensification of social exclusion.
Keywords: counter-movement; critique; double movement; globalization; political sociology